Quasi-two-dimensional magnetism and antiferromagnetic ground state in Li2FeSiO4 - Hergett, Waldemar; Bouldi, N.; Jonak, M.; Neef, C.; Ritter, C.; Abdel-Hafiez, M.; Seewald, F.; Klauss, H.-H.; Haverkort, Maurits W.; Klingeler, Rüdiger (Physical review, 2025)
Our experimental (neutron diffraction, Mössbauer spectroscopy, magnetic susceptibility, specific heat) and numerical studies on the evolution of short- and long-range magnetic order in 𝛾II−Li2⁢FeSiO4 suggest a quasi-two-dimensional (2D) nature of magnetism. The experimental data obtained on single crystals imply long-range antiferromagnetic order below 𝑇N=17 K. A broad maximum in magnetic susceptibility 𝜒 at 𝑇m≃28 K, observation of magnetic entropy changes up to 100 K, and anisotropy in 𝜒 are indicative of low-dimensional magnetism and suggest short-range magnetic correlations up to 200 K. Neutron diffraction shows that long-range antiferromagnetic order is characterized by the propagation vector 𝐤=(12,0,12). The ordered moment 𝜇=2.50⁢(2) 𝜇B/Fe, at 𝑇=1.5 K, is along the crystallographic 𝑎 axis. This is consistent with the observed static hyperfine field of 𝐵hyp=14.8⁢(3)⁢T by Mössbauer spectroscopy which indicates significant orbital contributions. The temperature dependence of 𝐵hyp yields the critical exponent 𝛽=0.116⁢(12) which is in the regime of the 2D Ising behavior. LSDA+U studies exploiting the experimental spin structure suggest dominating magnetic exchange coupling within the 𝑎⁢𝑐 layers (i.e., 𝐽3≃−6 K and 𝐽6≃−2 K) while interlayer coupling is much smaller and partly frustrated. This confirms the 2D nature of magnetism and is in full agreement with the experimental findings.